Multiple Sessions of Transcranial Direct Current Stimulation (tDCS) Reduced Craving and Relapses for Alcohol Use: A Randomized Placebo-Controlled Trial in Alcohol Use Disorder - Klauss, Jaisa; Anders, Quézia S.; Felippe, Luna V.; Nitsche, Michael A.; Nakamura-Palacios, Ester M. (Frontiers in Pharmacology, 2018)
Background: Transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique, has been studied as an adjunctive therapeutic agent for alcohol dependence. In a previous study, we showed that five consecutive sessions of tDCS applied bilaterally over the dorsolateral prefrontal cortex (dlPFC) reduced relapse to the use of alcohol in alcohol use disorder (AUD) outpatients. However, no changes on craving scores were observed. In the present study, we investigated if an extended number of sessions of the same intervention would reduce craving and relapses for alcohol use in AUD inpatients. Methods: Thus, a randomized, double-blind, sham-controlled, clinical trial with parallel arms was conducted (https://clinicaltrials.gov/ct2/show/NCT02091284). AUD patients from two private and one public clinics for treatment of drug dependence were randomly allocated to two groups: real tDCS (5 × 7 cm2, 2 mA, for 20 min, cathodal over the left dlPFC, and anodal over the right dlPFC) and sham-tDCS. Real or sham-tDCS was applied once a day, every other day, in a total of 10 sessions. Craving was monitored by a 5-item obsessive compulsive drinking scale once a week (one time before, three times during and once after brain stimulation) over about 5 weeks. Results: Craving scores progressively decreased over five measurements in both groups but were significantly reduced only in the real tDCS group after treatment. Corrected Hedges' within-group (initial and final) effect sizes of craving scores were of 0.3 for the sham-tDCS and of 1.1 for the real tDCS group. Effect size was 3-fold larger in the real tDCS group. In addition, the between-group analysis on craving score difference was nearly significant, and the effect size was 0.58, in favor for a larger effect in the real tDCS group when compared to sham-tDCS. Furthermore, in a 3-months follow-up after intervention, 72.2% of sham-tDCS group relapsed to the alcohol use whereas 72.7% of tDCS group were abstinent. Conclusions: Multiple sessions of bilateral prefrontal tDCS were well tolerated with no significant adverse events. Thus, extended repetitive bilateral tDCS over the dlPFC is a promising adjunctive clinical tool that could be used to reduce alcohol craving and relapses and facilitate alcoholism cessation.